ANALISIS PROYEK STEAM KINCIR ANGIN DAN JEMBATAN DALAM MENINGKATKAN KREATIVITAS DAN KOLABORATIF SISWA - Anggraini, Shinta; Musfita, Cindi; Alim, Jesi Alexander; Anggriani, Mitha Dwi (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2025)
The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach integrates various disciplines to create a holistic and interdisciplinary learning experience. In the context of elementary education, projects such as constructing wind turbines and mini bridges provide opportunities for students to apply scientific and technical concepts in practical projects. Through the wind turbine project, students learn about the principles of physics and engineering in designing and building models that can generate energy. Meanwhile, the mini bridge project teaches students about structure and material strength, as well as the importance of design in engineering. Both projects require students to collaborate in groups, divide tasks, and solve problems collaboratively. Implementing the STEAM approach in these projects has proven effective in enhancing students' 21st-century skills, such as critical thinking, creativity, communication, and collaboration. Furthermore, this approach also increases students' motivation and interest in learning, as they can directly see the practical applications of the concepts being studied. Overall, STEAM-based projects like wind turbines and mini bridges not only enrich students' learning experiences but also prepare them to face future challenges with relevant and applicable skills.